De Novo DNMTs and DNA Methylation: Novel Insights into Disease Pathogenesis and Therapy from Epigenomics - Leppert, Sylwia; R. Matarazzo, Maria (Current Pharmaceutical Design, 2014)
DNA methylation plays an important role in epigenetics signaling, having an impact on gene regulation, chromatin structure and development. Within the family of de novo DNA methyltransferases two active enzymes, DNMT3A and DNMT3B, are responsible for the establishment of the proper cytosine methylation profile during development. Defects in DNMT3s function correlate with pathogenesis and progression of monogenic diseases and cancers. Among monogenic diseases, Immunodeficiency, Centromeric instability and Facial anomalies (ICF) syndrome is the only Mendelian disorder associated with DNMT3B mutations and DNA methylation defects of satellite and non-satellite regions. Similar CpG hypomethylation of the repetitive elements and gene-specific hypermethylation are observed in many types of cancer. DNA hyper-methylation sites provide targets for the epigenetic therapy. Generally, we can distinguish two groups of epi-drugs affecting DNMTs activity, i) nucleoside inhibitors, covalently trapping the enzymes, and bringing higher cytotoxic effect and (ii) nonnucleoside inhibitors, which block their active sites, showing less side-effects. Moreover, combining drugs targeting chromatin and those targeting DNA methylation enhances the efficacy of the therapy and gives more chances of patient recovery. However, development of more specific and effective epigenetic therapies requires more complete understanding of epigenomic landscapes. Here, we give an overview of the recent findings in the epigenomics field, focusing on those related to DNA methylation defects in disease pathogenesis and therapy.
Keywords: DNA methylation